(untitled) (Educational Dimension, 2023)
The paper is devoted to using innovative technologies in the professional training of future ship engineers. It highlights the need for tutors to make lessons interesting and exciting and to create a situation where every cadet can be active. The research emphasises that the main target of maritime education today is not just to accumulate knowledge and skills but to prepare cadets as independent subjects of educational activity who can learn and upgrade their knowledge. The article describes the benefits of digital technologies for online maritime education and training, including various videoconference services. It also discusses the psychological theory of learning based on the psychology of human relationships, which is crucial to interactive learning technologies. The paper concludes by describing various technologies for information visualisation, such as cloud technologies and gamification, and recommends tools like Mentimeter, Aha Slides, and Poll Everywhere for collaborative work and knowledge exchange. The research also suggests that using whiteboard resources during Maritime English lessons can serve cadets as a visual platform for displaying essential Maritime English vocabulary, supporting interactive discussions, conducting simulated exercises and role-playing scenarios.